GE_GERICHTE P/14688/2016 vom 17. Februar 2023 - GE Cour de justice (2023)
VIOL;FIXATION DE LA PEINE;PRINCIPE DE LA CÉLÉRITÉ;PEINE PRIVATIVE DE LIBERTÉ;TORT MORAL;DÉFENSE D'OFFICE | CP.190.al1; CP.47; CPP.5.al1; CP.43; CO.49; CPP.135; CPP.138; CPP.428